Advisory system development for reliable FEM modelling in aerospace - Hetey, Laszlo; Campbell, James; Rade, Vignjevic (Emerald, 2015)
This paper aims to describe the development of an advisory system that helps building sound finite element (FE) models from computer-aided design data, with actual uncertainty levels expressed by error values in per cent, as today there is no widely accepted tool for FE idealisation error control.
Keywords: Advisory system; Expert system; Modelling; FEM; Idealisation; Error control